Fatty acid content of Creole-Nubia goat milk with different seasonal diets in an intensive feeding system in an arid region - Ortega-Pérez, Ricardo; Toyes-Vargas, Eduardo; Espinoza-Villavicencio, José; Palacios-Espinosa, Alejandro; Montes-Sánchez, Juan; Murillo-Amador, Bernardo (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
The objective is to determine the seasonal-diet effect (dry, rainy) on goats’ milk fatty acid profile reared on a farm with an intensive production system located in an arid zone of Mexico. In the rainy season, a group of 10 goats, Creole × Anglo-Nubian, consumed a diet composed exclusively of alfalfa hay (Medicago sativa). Meanwhile, in the dry season, a similar goat group ate a mixture of corn (Zea mays) and sorghum grains (Sorghum bicolor), and buffel grass hay (Cenchrus ciliaris) in a 1:1:1 ratio. The goats were between 90 and 180 days of lactation. The saturated, monounsaturated, polyunsaturated, and branched-chain fatty acids in milk were measured. The rainy-season milk showed a higher content of fatty acids; however, the contents of most types of fatty acids were not significant between seasons, except for the polyunsaturated (18:2 n-6, a-linoleic acid) and highly unsaturated fatty acids (arachidonic, eicosapentaenoic, and docosahexaenoic acid).